UAT prospective and change in the public policy framework - Lladó-Lárraga, Dora María (Universidad Autónoma de Tamaulipas, 2018)
This is a case of the Universidad Autonoma de Tamaulipas Mexico (UAT) on how global trends and educational policies translate into specific actions that guide the direction of the institution. In the introduction, there is an explanation of UAT ́s inception and the approach structure of the topic. The second part describes the global trends in higher education, that reflect the reality of higher education institutions in different countries. Then we analyze the policies and trends of higher education in Mexico to demonstrate how they are a representation of the problems and cautioned directions in the global context. The third part describes the process of implementing the educational policies in the university ́s academic reform, the process of change, and their gradual incorporation. In conclusion, there are some elements that outline pending challenges to work in order to achieve the mission and institutional policies.